1997
DOI: 10.1007/bf02763981
|View full text |Cite
|
Sign up to set email alerts
|

Experimental in vivo fenestration of guinea pig cochlea using 2.79 Μm laser radiation

Abstract: Abstract. Erbium-YSGG laser systems are promising tools in ear, nose and throat (ENT) surgery. The high absorption in biological tissues, resulting in precise tissue ablation with minimal thermal tissue damage, and the possibility to guide the radiation through optical fibres make the 2.79 ~m wavelength a favourite for microsurgery.In order to simulate the fenestration of the human stapes foot plate required for prosthesis implantation when treating otosclerosis, five guinea pig cochleae were irradiated in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Therefore, in the last 2 decades, more than a few experimental and clinical studies to establish the safety of different lasers and to find the "ideal laser" for primary and revision stapedotomy have been performed. [13][14][15][16][17][18][19][20] Comparison of preoperative with early (3 days) and late (12 months) postoperative bone conduction, assessed up to 4000 Hz, showed in most of the patients unchanged or slightly improved values, both in the early and in the late measurements. Only 1 patient showed a deterioration of more than 10 dB, also in the late measurement, and it was related to the high number of pulses (the highest of our study group) that were applied to perforate his thick footplate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, in the last 2 decades, more than a few experimental and clinical studies to establish the safety of different lasers and to find the "ideal laser" for primary and revision stapedotomy have been performed. [13][14][15][16][17][18][19][20] Comparison of preoperative with early (3 days) and late (12 months) postoperative bone conduction, assessed up to 4000 Hz, showed in most of the patients unchanged or slightly improved values, both in the early and in the late measurements. Only 1 patient showed a deterioration of more than 10 dB, also in the late measurement, and it was related to the high number of pulses (the highest of our study group) that were applied to perforate his thick footplate.…”
Section: Discussionmentioning
confidence: 99%
“…With laser pulses between 10 and 17 J/cm 2 , it is possible to perforate the stapes without damaging the cochlear function. 11,20 Other experimental studies show that during laser application, sudden molecular disruption produces an acoustic shock with varying sound levels for different laser systems. Measurement using sound pressure level (SPL) recording equipment to record laser beam noises on bovine stapes revealed sound levels of 133 dB SPL for erbium laser, 135 dB SPL for CO 2 , and 92 dB SPL for argon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients suffered from classical otosclerosis and had a moderate conductive hearing loss with negative Rinne preoperatively. J/cm 2 ) applied to the inner ear liquid destroyed the cochlea (18). Based on these results, we concluded that the maximum erbium laser power allowed for use in stapes surgery was 10-17 J/cm 2 .…”
Section: Patientsmentioning
confidence: 72%